Mali : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Annex for Mali examines recent economic developments in Mali. The paper highlights that since the early 1990s, Mali has made appreciable progress in reducing macroeconomic imbalances and liberalizing the economy. This has been made possible by consolidating the government fiscal position, lowering inflation, dismantling public monopolies, abolishing price controls, liberalizing the trade regime, and allowing for a greater role for private sector initiative. However, the pace of the country's development remains constrained by a low level of human capital, inadequate infrastructure, and high energy and telecommunications costs.